No First Use and Credible Deterrence - Steve Fetter (Journal for Peace and Nuclear Disarmament, 2018)
Despite progress in reducing the number of nuclear weapons in the largest arsenals, a number of states are now looking to increase their reliance on nuclear weapons not only for deterrence, but also for coercion or war fighting.  There is scant evidence that nuclear weapons are effective or well suited for these roles, and the risks of relying on nuclear weapons for more than deterrence of nuclear attack are under appreciated.  We review the evolution of US nuclear strategy and assesses the prospects for establishing a policy of no first use.  A no first use policy would in no way reduce deterrence of nuclear attack against the United States or its allies.  Nuclear weapons are not an effective deterrent against non-nuclear attack because there are few if any scenarios in which a US threat to use nuclear weapons first in response to non-nuclear aggression against the United States or its allies would be credible.  The benefits of adopting a policy of no first use include reducing the risks of accidental nuclear escalation or nuclear use from miscalculation, as well as supporting nonproliferation and disarmament efforts.